Iowa Birdline update, January 30, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Email for the Iowa Birdline update for January 30, 1995. Highlights of the update include sightings of the continued presence of the Common Eider, Varied Thrush, Snowy Owl and Bohemian Waxwing. Also included are handwritten notes with sightings of five Short-eared Owls, an adult Northern Goshawk and a second winter Glaucous Gull. Epson - sheet feed/flatbed